2023
DOI: 10.1002/adfm.202212193
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial and Antibiofilm Nanoparticles Assembled from Naturally Occurring Building Blocks

Abstract: Bacterial infections represent one of the serious human healthcare threats, and ≈80% of bacterial infections are related to biofilm. So far, there are extensive investigations on the development of robust biomaterials toward the elimination of biofilms and synergistic antibacterial applications. Despite the progress made, concerns have always been raised regarding the sophisticated synthesis and pre‐modification of hybrid materials, complicated purification and high‐cost work. In this study, a series of robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In this study, natural polyphenol PCA was used to directly react with PMB, a common type of antibiotic with minimal drug resistance, to create multifunctional NPs for the treatment of peritonitis-induced sepsis (Figure a). Given the rich chemical structure of PCA and the large number of amino groups within PMB, both of them could serve as structural as well as functional synthons to build up the targeted NPs via multiple Schiff base interactions as well as the polyphenol’s self-polymerization reaction. , The SEM results (Figure b) showed that the resulting NPs possessed uniform spherical morphologies. By adjusting the incubation time during the fabrication process, the NPs’ size could be properly regulated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In this study, natural polyphenol PCA was used to directly react with PMB, a common type of antibiotic with minimal drug resistance, to create multifunctional NPs for the treatment of peritonitis-induced sepsis (Figure a). Given the rich chemical structure of PCA and the large number of amino groups within PMB, both of them could serve as structural as well as functional synthons to build up the targeted NPs via multiple Schiff base interactions as well as the polyphenol’s self-polymerization reaction. , The SEM results (Figure b) showed that the resulting NPs possessed uniform spherical morphologies. By adjusting the incubation time during the fabrication process, the NPs’ size could be properly regulated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the poor penetration of the nanomaterials into biofilm greatly limited the efficiency of combating BAIs. Various strategies have been developed to enhance the permeability of nanostructures, including controlling the size and shape, , polymer-targeted modification, matrix component-degrading enzyme decoration, liposome encapsulation, and polypeptide modification. Nanoparticles with sharp shapes were more likely to destroy the substrate structure of biofilm than blunt particles. , Recently, Qian et al synthesized a magnetic zeolitic imidazolate framework (ZIF) with a flower-like clustered structure for combating biofilm infections via combining the photothermal with catalytic properties, which demonstrated that the flower-like structure could destroy the local biofilm structure to increase the penetration . In addition, the sharp-shaped nanostructures equipped with magnetic nanoparticles provided enormous potential for biofilm destruction. Magnetic nanoparticles tunneled channels into the biofilm under an alternating magnetic field (AMF), thus improving the permeability of the antibacterial agent.…”
Section: Introductionmentioning
confidence: 99%
“…Natural polyphenols are a class of natural compounds widely present in plants, possessing a range of physical, chemical, and biological properties, such as metal chelation, antioxidant, and anti-UV. [13][14][15][16][17][18] Moreover, polyphenols containing two or more phenol structural units can effectively manipulate non-covalent and covalent interactions, enabling strong affinity towards various substrates and exhibiting high adhesive properties. [19][20][21][22] These multifunction and unique physicochemical properties of polyphenolic materials have been extensively researched and pursued in recent decades, resulting in the design of a series of conductive hydrogels with synergistically controlled stretchability, self-healing and selfadhesive properties.…”
Section: Introductionmentioning
confidence: 99%